The role of business education in shaping entrepreneurial intentions: examining psychological and contextual determinants among university students in Bangladesh - Ferdousi, Farhana; Rahman, Mehe Zebunnesa; Qamruzzaman, Md. (Frontiers in Education, 2025)
This study examines the influence of business education on entrepreneurial intentions among university students in Bangladesh, identifying key determinants, challenges, and policy implications for fostering entrepreneurship. A structured questionnaire was used to collect data over 6 months, employing Structural Equation Modeling (SEM) and Partial Least Squares (PLS-SEM) for hypothesis testing and analysis. Findings reveal that entrepreneurial education significantly enhances students’ self-efficacy, attitudes, and perceived behavioral control, directly impacting their entrepreneurial intentions. However, financial barriers and limited family support hinder entrepreneurial pursuits. Business education acts as a mediator, amplifying the effects of attitudinal and perceived control factors on entrepreneurial intentions. Additionally, the study confirms the moderating role of perceived social norms in shaping entrepreneurial behavior. The results emphasize the need for curriculum enhancements incorporating experiential learning, industry collaborations, and mentorship programs to bridge the intention-action gap. This research contributes novel insights by integrating the Theory of Planned Behavior (TPB) with entrepreneurial education in a developing economy context. Unlike prior studies, it empirically establishes the mediating role of business education, offering a nuanced understanding of entrepreneurial mindset formation. Policy recommendations include revising business education curricula to incorporate experiential learning, financial literacy, and entrepreneurial mentorship programs. Government support through accessible funding schemes and regulatory incentives is also essential to fostering youth entrepreneurship.